Passion and compassion : mga tula sa Ingles at Pilipino - Lanot, Marra PL. (Quezon City)
The Postcolonial Perverse is a two-volume collection of fifteen different critiques of varying (3z(Baspects(3y (Bof contemporary Philippine culture. The work$1 (Bs (3z(Beclectic(3y (Btopics range from the independent cinema movement to the mystifications of nationalist poetics, from sacrilegious (3z(Bavant-garde(3y (Bart to the deconstruction of an inaugural text in the Philippine anglophone tradition, and from reflections on the contact zone between science and art to the impertinent question of our foremost national hero$1 (Bs quizzical gender and sexual identity. The title$1 (Bs two concepts$1 (3z(Bpostcolonial(3y (Band (3z(Bperverse(3y$1 (Bare almost symmetrically split across these two books, urging the reader to more sharply intuit and (3z(Bexperience(3y (Bthe project$1 (Bs central theme. Namely: that the postcolonial hybridity or cultural mixedness that characterizes Philippine life is the same thing as the perverse inability of its agents to stay committed to principled and categorical thought. In the Preface the author, Professor J. Neil C. Garcia, offers the reading that it is perhaps our culture$1 (Bs relatively recent and uneven literacy$1 (Bas well as its enduring residual orality$1 (Bthat has brought this (3z(Bperverse(3y (Bsituation about, rendering Filipino social memory fluid and malleable on one hand, and social relations and norms eminently negotiable on the other. And yet, what$1 (Bs interesting is that it is precisely upon this ambivalent cultural ground that Filipinos must endeavor to fashion their sense of collective being$1 (Bwhich is to say, their national identity. s
Keywords: Philippine poetry